Fraud Risk Analysis Fraud Prevention Detection with Fraud Triangle and Financial Ratios at PT. Garuda Indonesia (Persero) Tbk. - Eko Gumaya Sari (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
This study aims to detect the risk of fraud in the financial statements and ongoing fraud prevention measures if there are irregularities in the financial statements. The issue of earnings management in the financial statements of PT Garuda Indonesia (Persero) Tbk by significantly increasing profits has raised a lot of suspicion and greatly harmed many parties, especially investors who invested in this company. The analysis was carried out using the fraud triangle variable and by asking for opinions from experts in their respective fields or professions related to fraud, such as auditors, accounting staff and employees who assist in the presentation of financial statements. The sample included 30 respondents. The calculation of financial ratios was done by calculating the ratio of liquidity, profitability, and solvency to detect fraud risk. The results of the analysis of fraud detection during the 2017-2019 period showed that there was an indication of markups on the company’s capital and profits in 2019. During those three years there was a decline in the company’s performance including its effectiveness in paying its short-term debt. This is in line with the opinion of auditors and users of financial statements who have predicted fraud and profit markups in the financial statements.